Differences in phenotypes, symptoms, and survival in patients with cardiomyopathy—a prospective observational study from the Sahlgrenska CardioMyoPathy Centre - Ljungman, C.; Bollano, E.; Rawshani, A.; Nordberg Backelin, C.; Dahlberg, P.; Valeljung, I.; Björkenstam, M.; Hjalmarsson, C.; Fu, M.; Mellberg, T.; Bartfay, S.-E.; Polte, C. L.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Cardiomyopathy is the fourth most common cause of heart failure. The spectrum of cardiomyopathies may be impacted by changes in environmental factors and the prognosis may be influenced by modern treatment. The aim of this study is to create a prospective clinical cohort, the Sahlgrenska CardioMyoPathy Centre (SCMPC) study, and compare patients with cardiomyopathies in terms of phenotype, symptoms, and survival. Methods The SCMPC study was founded in 2018 by including patients with all types of suspected cardiomyopathies. This study included data on patient characteristics, background, family history, symptoms, diagnostic examinations, and treatment including heart transplantation and mechanical circulatory support (MCS). Patients were categorized by the type of cardiomyopathy on the basis of the diagnostic criteria laid down by the European Society of Cardiology (ESC) working group on myocardial and pericardial diseases. The primary outcomes were death, heart transplantation, or MCS, analyzed by Kaplan–Meier and Cox proportional regression, adjusted for age, gender, LVEF and QRS width on ECG in milliseconds. Results In all, 461 patients and 73.1% men with a mean age of 53.6 ± 16 years were included in the study. The most common diagnosis was dilated cardiomyopathy (DCM), followed by cardiac sarcoidosis and myocarditis. Dyspnea was the most common initial symptom in patients with DCM and amyloidosis, while patients with arrhythmogenic right ventricular cardiomyopathy (ARVC) presented with ventricular arrythmias. Patients with ARVC, left-ventricular non-compaction cardiomyopathy (LVNC), hypertrophic cardiomyopathy (HCM), and DCM had the longest time from the debut of symptoms until inclusion in the study. Overall, 86% of the patients survived without heart transplantation or MCS after 2.5 years. The primary outcome differed among the cardiomyopathies, where the worst prognosis was reported for ARVC, LVNC, and cardiac amyloidosis. In a Cox regression analysis, it was found that ARVC and LVNC were independently associated with an increased risk of death, heart transplantation, or MCS compared with DCM. Further, female gender, a lower LVEF, and a wider QRS width were associated with an increased risk of the primary outcome. Conclusions The SCMPC database offers a unique opportunity to explore the spectrum of cardiomyopathies over time. There is a large difference in characteristics and symptoms at debut and a remarkable difference in outcome, where the worst prognosis was reported for ARVC, LVNC, and cardiac amyloidosis.